2018
DOI: 10.15694/mep.2018.0000219.1
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Internship Preparedness Program for Final Year Medical Students

Abstract: Introduction: Medical students undertake extensive training yet often feel they lack the practical non-medical skills required for successful transition to internship. While research provides evidence for student perceptions and experiences regarding internship, there is little information regarding how students can be 'taught' work-readiness through learning non-medical skills.Methods: By reducing cognitive load when structured using a flipped classroom method, active learning resources may provide an effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Interestingly, the program has become a fundamental program and developers were given incentives to continue their development (21). A Dutch study was conducted to study the perceptions of general practitioners (GP) trainers through blended learning interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the program has become a fundamental program and developers were given incentives to continue their development (21). A Dutch study was conducted to study the perceptions of general practitioners (GP) trainers through blended learning interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Goldie (2012) observes that "students' professional identity formation is influenced more by the informal and hidden curricula than formal teaching experiences" (p. 645), and some of the interns' comments suggested that their understanding of professional medical communication had been shaped by the hidden curriculum of medical education, where memorisation of large volumes of material is seen as essential (Nasir et al, 2018;Qiao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%